Molecular characterization of two insect nematode species (Oxyurida: Thelastomatidae) using small subunit (18S) ribosomal DNA sequence and secondary-structure analyses. Issue 2 (June 2014) - Chaudhary, A.; Singh, N.; Singh, H.S.
Abstract Nematodes of the family Thelastomatidae are parasitic in the alimentary tract of many arthropods, including Periplaneta americana L. In Meerut, Uttar Pradesh, India, two nematode species, namely Hammerschmidtiella indicus and Thelastoma icemi, belonging to this family have been reported. In the present study, the molecular phylogeny of these two nematode species was derived using small subunit (18S) sequence and secondary-structure analyses. The small subunit sequence analyses were carried out to explore the validation and systematics of these species. Phylogenetic analyses were performed for primary sequence data as well as using neighbour-joining and maximum-parsimony approaches. In contrast, the inferred secondary structures for the two species, using free-energy modelling, showed structural identities. As well as this, motif sequences were also found to be a promising tool for nematode species identification. The study provides molecular characterization based on primary sequence data of the 18S ribosomal DNA region of the nematodes along with secondary-structure data and motif sequences for inferences at higher taxonomic levels.